Control of Nipah Virus Infection in Mice by the Host Adaptors Mitochondrial Antiviral Signaling Protein (MAVS) and Myeloid Differentiation Primary Response 88 (MyD88). (19th December 2019) - Iampietro, Mathieu; Aurine, Noemie; Dhondt, Kevin P; Dumont, Claire; Pelissier, Rodolphe; Spanier, Julia; Vallve, Audrey; Raoul, Herve; Kalinke, Ulrich; Horvat, Branka
Abstract: Interferon (IFN) type I plays a critical role in the protection of mice from lethal Nipah virus (NiV) infection, but mechanisms responsible for IFN-I induction remain unknown. In the current study, we demonstrated the critical role of the mitochondrial antiviral signaling protein signaling pathway in IFN-I production and NiV replication in murine embryonic fibroblasts in vitro, and the redundant but essential roles of both mitochondrial antiviral signaling protein and myeloid differentiation primary response 88 adaptors, but not toll/interleukin-1 receptor/resistance [TIR] domain–containing adaptor–inducing IFN-β (TRIF), in the control of NiV infection in mice. These results reveal potential novel targets for antiviral intervention and help in understanding NiV immunopathogenesis.